Peran Tuha Peut Dalam Pengembangan Reusam Perlindungan Anak Yang Berhadapan Dengan Hukum (ABH) Di Aceh Besar - Mansari Mansari (Universitas Trunojoyo Madura, 2018)
Some gampongs in Aceh Besar have established gampong reusam on child protection in written form. Reusam which usually regulates public behavior about habits undertaken by the public in an unwritten form, is now beginning to be written in written form. The formation of gampong reusam was formed by Tuha Peut Gampong which was discussed together with the keuchik and community leaders of the gampong. This research aims to find out how the process of reusam formation of child protection in Aceh Besar and how the role of Tuha Peut in determining the direction of development of child protection reusam in Aceh Besar. This research uses qualitative research with data source from primary data obtained through interview with Keuchik, Tuha Peut Gampong and Female Woman. Secondary data is obtained through documentation studies in the library. The results showed that the process of forming a village reusam on Child Protection was established through the involvement of elements and community leaders, even women were involved in the preparation. Tuha Peut has an important role in the development of a gampong reusam that adopts local and applicable local values in Aceh. These values are deliberation, mediation and the use of adat sanctions for child offenders in cases that occur, such as Advice, Warning, apology, fines, compensation, returned to the family, Establishment of Child Protection Committees dealing with law and engagement government agencies.